The Use of Agile Models in Software Engineering: Emerging and Declining Themes - Ay, Sevinç (Prof.Dr. İskender AKKURT, 2024)
Software engineering is a systematic discipline that covers the creation of a software product at the end of software development processes. Many different models are used in software development processes. The most widely used model today is the Agile Approaches model. Methods that focus on increasing customer orientation and speed in software development projects are considered agile approaches. Agile approaches are used to overcome the limitations of traditional methods such as the waterfall approach and to adapt to constantly changing requirements. Agile approaches increase collaboration in a project team established to develop a software product and contribute to product success by increasing customer satisfaction. Agile approaches are highly preferred for distributed software development environments and remote teams. The reviewed literature shows that agile approaches increase flexibility and speed of delivery in software engineering projects, but they also bring many difficulties when they are not applied with an expert team in large-scale projects or when they are applied incorrectly. Agile approaches have transformed software engineering processes, prioritizing customer requirements and supporting high quality software development processes. However, factors such as the experience of teams, organizational culture and process management skills are critical for the successful implementation of agile methods. Within the scope of the study, bibliometric analysis was conducted on 1372 data obtained from the Web of Science database. While the prominent fields of study in the study were “software development”, “information-systems” and “decision-making”, the themes that are about to disappear were “management” and “framework”. The study provides a roadmap for future applications of agile methods in software engineering. © 2024, Prof.Dr. İskender AKKURT. All rights reserved.
Keywords: Agile Approaches; Agile Software; SCRUM; Software Engineering